Microplastics in Indonesia's Aquatic Ecosystems: Hidden Threats to Human Health and Environmental Sustainability - Asramid Yasin; Amelia Retno Eka Putri; Mario Zulhadi Amrullah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Microplastics have become a widespread environmental threat in Indonesia's aquatic ecosystems, an archipelagic country that has historically and recently been recorded as one of the world's major contributors to plastic pollution. Although studies on the presence of microplastics in Indonesian waters have been quite developed in terms of the quantity of publications, synthesis that specifically integrates the dimensions of human health and environmental sustainability in an integrated manner is still relatively limited, making it difficult to formulate a comprehensive picture for research and policy development. This study aims to identify the distribution and characteristics of microplastics in Indonesia's aquatic ecosystems, analyze their impact on human health, and examine their implications for environmental sustainability. The approach used is Systematic Literature Review (SLR) following the PRISMA protocol with the PICOS framework, covering articles published in the range of 2017–2026. Of the 64 articles identified, 15 primary studies were obtained along with one comparative narrative review that was synthesized thematically. The results of the synthesis show that microplastics are widespread ranging from small rivers to open seas, with local anthropogenic pressures, rather than the mere presence of water bodies, as the main determinant of pollution intensity, while mangrove areas consistently function as natural accumulation points. In the health dimension, the consumption of marine products was identified as the most documented route of exposure, although the level of quantifiable risk was still limited by the lack of Indonesia's population-based toxicology reference values. This synthesis also reveals significant geographical biases, with the majority of studies concentrated on the island of Java.